Rada sądownictwa w Holandii - Bień-Kacała, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The paper presents the Dutch Council for the Judiciary. The Dutch Council for the Judiciary is a body with a relatively short tradition. It began operating on 1 January 2002. The Council for the Judiciary is seen as a link between the Minister of Justice and the courts. It was created to ensure separation in the relations between these bodies.The matters of judicial administration should be dealt with by the judiciary itself. The author describes the position and competences of the Council.
Keywords: Netherlands; judiciary; council of judiciary; impartiality of the court expert; judicial independence